Fate of indeterminate microbial keratitis - Jain, Shikha; Pathak, Ashok; Mammel, Anwara; Malhotra, Shalini (International Journal of Research in Medical Sciences, 2022)
Background: Previous published literature has shown that there is no significant difference between outcomes of culture positive and culture negative infective keratitis. This study was done to find the outcome in cases of indeterminate keratitis in our institute. Purpose was to highlight the fate of indeterminate microbial keratitis. Methods: Patients presenting to cornea services of ABVIMS and Dr. RML hospital from February 2017 to April 2021 were evaluated for demographic and microbiological assessment, clinical presentation and management. Results: The 188 out of 310 cases were microbiologically positive. No organism could be detected in 122 cases. Clinical prognosis is worse in cases of indeterminate keratitis. Conclusions: Cases with indeterminate microbial keratitis do not show timely and appropriate response which leads to spread of infection resulting in more complications and less CDVA.